Proof of theorems in school and university mathematics courses аs a method for improving the results of studies - M. A. Prihodovsky (Moscow Polytechnic University, 2022)
The article touches upon a problem of the relationship between the study of proofs and understanding of methods for solving practical problems in schools and universities mathematics courses.